Controlling 3-phase induction motor using sinusoidal pulse width modulation method / Mohd Zaid Zakaria - Zakaria, Mohd Zaid (2009)
This thesis presents a simple constant volt per hertz control, sinusoidal pulse width modulation output voltage for a three-phase induction motor drive. Essentially an open loop speed control scheme was adopted. The constant V/f speed control involves simultaneous adjustment of voltage and supply frequency in order to achieve variable speed with constant torque. The constant volt per hertz (V/f) method is an effective method for AC motor drive speed regulation. The PIC16F877A microcontroller from microchip was used to generate the SPWM signal to implement the control scheme. Also simple techniques for generating the modulation waves of SPWM methods are described.